Studi Analisis Kebutuhan Pengembangan Media Pop Up Kebudayaan Berbasis Audio sebagai Penanaman1) Karakter Budaya untuk SD Kelas 4 - Endah Istiqomah; Hindun Nur ‘Aisyah; Nur Milati (Jurnal VARIDIKA, 2019)
Culture is the identity of a nation, there are more than 633 large ethnic groups in Indonesia (www.bps.go.id). But there have been many Indonesian cultures that have been claimed by other countries. The low understanding of Indonesia’s young generation towards culture is one of the problems faced today. Therefore the young generation needs to be reintroduced about its culture. The lack of learning media makes students’ motivation in learning culture low. This study aims to: 1) conduct an analysis of the students’ lack of interest in Indonesian culture, and 2) see the need for cultural media as planting cultural characters in the 4th grade. This research uses descriptive quantitative method which describes the low awareness of students towards culture. The subject of this study was 4th grade students at SD N Triharjo. Based on the results of media needs, the accumulation of students understanding culture is 31.17% due to the lack of learning media about culture. The existence of Pop Up media is expected to help teachers in introducing culture among elementary students.